The basics of information security : understanding the fundamentals of InfoSec in theory and practice - Andress, Jason (Waltham, MA : Syngress, 2014)
As part of the Syngress Basics series, The Basics of Information Security provides you with fundamental knowledge of information security in both theoretical and practical aspects. Author Jason Andress gives you the basic knowledge needed to understand the key concepts of confidentiality, integrity, and availability, and then dives into practical applications of these ideas in the areas of operational, physical, network, application, and operating system security. The Basics of Information Security gives you clear-non-technical explanations of how infosec works and how to apply these principles whether you're in the IT field or want to understand how it affects your career and business. The new Second Edition has been updated for the latest trends and threats, including new material on many infosec subjects.
Mandatory access controlMore advanced; Role-based access control; Attribute-based access control; Multilevel access control; Physical access controls; Authorization and access control in the real world; Summary; Exercises; References; 4 Auditing and Accountability; Introduction; Accountability; More advanced; Security benefits of accountability; Nonrepudiation; Deterrence; More advanced; Intrusion detection and prevention; Admissibility of records; How we accomplish accountability; Auditing; What do we audit?; Alert!; Logging; Monitoring; Assessments.
Online resource; title from PDF title page (ScienceDirect, viewed May 30, 2014).
Includes index.
Includes bibliographical references and index.
Keywords: Computer security; Computer networks -- Security measures; Information technology -- Security measures; Information resources management; Computer science; COMPUTERS -- Internet -- Security; COMPUTERS -- Networking -- Security; COMPUTERS -- Security -- General; Computer networks -- Security measures; Computer science; Computer security; Information resources management; Information technology -- Security measures; Computer Security; Information Management; Electronic books